Creating a successful digital presence : objectives, strategies and tactics - Fletcher, Gordon; Adolphus, Noel, 1975- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Increasingly graduates, and anyone who is entering employment, need an individual digital presence to stand out and showcase themselves to secure their first professional role. This book takes an employability approach to encourage those currently studying, or about to enter the world of work, to develop a set of skills that enables them to recognise and deliver an effective digital presence, firstly for themselves and then for the organisations who would employ them. It does not assume any prior technical knowledge and emphasises the value and benefits of creating a presence to actively participate in the digital economy. By structuring the chapters incrementally, the reader is guided through the development of their own presence while also being given the concepts and tools that will enable them in the future to scale this activity to suit the needs of a start-up, an SME or a social business. By using well-established business principles to design a strategy, the reader is guided through the creation of a personal Theory of Change that will enable them to turn an abstract goal into an individual digital presence through a defined series of stages and intermediate change objectives. The book then proposes a series of tactics to draw out concrete actions. A range of examples and case studies from around the world feature in each chapter to showcase the range of different types of digital presence that can be created. By using a strategic and systematic process, this book draws together academic thinking with tangible and highly practical outcomes. It is essential reading for advanced undergraduate and postgraduate students studying any discipline related to the digital world, particularly digital marketing and digital business, entrepreneurship and strategy, as well as those taking employability and personal professional development programmes"--
OCLC-licensed vendor bibliographic record.
Keywords: Public relations; Social media; Branding (Marketing); Internet in public relations; Internet marketing; BUSINESS & ECONOMICS / E-Commerce / Internet Marketing; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Business Communication / General